Relapsed Waldenstrom’s Macroglobulinemia and Therapy-Related Myelodysplastic Syndrome with Complex Cytogenetics: A Treatment Dilemma - Shreyas Kalantri; Inderpreet Singh; Long Yang; Khadega A. Abuelgasim (Case Reports in Oncology, 2023)
Waldenstrom’s macroglobulinemia (WM) is a lymphoplasmacytic lymphoma characterized by the infiltration of the bone marrow by clonal lymphoplasmacytic cells that produce monoclonal immunoglobulin M as defined by the World Health Organization Classification of hematological malignancies. Historically, the treatment options for WM were limited to alkylating agents and purine analogs. The introduction of immune therapy, including CD20 targeted therapy, proteasome inhibitors, and immune modulators, has provided benefit to those patients and has now become the standard of care. As WM patients become long-term survivors, treatment’s late toxicities have become more apparent. Here, we report a case of a 74-year-old female who presented to the hospital with fatigue and was diagnosed with WM. She was treated with bortezomib, doxorubicin, and bendamustine, followed by rituximab. After a remission period of 15 years, the patient had a relapse of WM, and bone marrow biopsy findings were consistent with intermediate-risk t-MDS with complex cytogenetics, presenting us with a treatment dilemma. We decided to treat WM, and the patient went into VGPR with residual lymphoma cells. Despite having dysplasia and complex cytogenetics, she did not have any cytopenia. Currently, she is under observation anticipating the progression of her MDS, given her intermediate I risk status. This case features the occurrence of t-MDS after therapy with bendamustine, cladribine, and doxorubicin. This highlights the need for closer monitoring and consideration of long-term adverse effects when treating patients with indolent lymphomas, especially WM. Late complications need to be considered, and risk versus benefit analysis needs to be carefully evaluated, especially in younger patients with WM.